The value of supplementary trace minerals in a fattening ration - Carmack, B.D.; Smith, E.F.; Koch, B.A.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Forty head of good-to-choice Hereford yearling heifers were divided into four lots, 10 in each lot, on the basis of weight and previous treatment. The heifers were purchased near Fort Davis, Texas, as calves the fall of 1958. They were wintered and summer grazed on bluestem pastures near Manhattan before the experiment.
Keywords: Beef; Trace minerals; Gain; Carcass